ANALISIS KONDISI LINGKUNGAN FISIK TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN MANUFAKTUR DI MAKASSAR - Muhammad Tamrin (Movere Journal, 2022)
This study aims to analyze the effect of the relationship between physical environmental conditions on the performance of employees in manufacturing companies in Makassar, either partially or simultaneously. This research is an explanatory research using a quantitative approach and data collection techniques through questionnaires and observations. The population in this study was 350 people with a sampling technique using simple random sampling where the population was sampled without looking at the criteria of the entire population with a sample of 350 people. Hypothesis testing using SPSS tools. The results showed that the condition of the physical environment had a positive and significant effect on employee performance at the PT. Sinar Sulawesi in Makassar City.